A Qualitative Evaluation of Holiday Breakfast Clubs in the UK: Views of Adult Attendees, Children, and Staff - Defeyter, Margaret Anne; Graham, Pamela Louise; Prince, Kate (Frontiers in Public Health, 2015)
Across the UK, 1.3 million children access free school meals for around 38 weeks of the year. However, during school holidays, many families face considerable difficulties in providing a consistent and nutritious supply of food for their children, particularly during the extended summer break. In an effort to address this issue, a number of community-based breakfast clubs were set-up across the North West of England and in Northern Ireland where people could access a free breakfast meal during the summer holidays. Qualitative interviews were carried out with 17 children, 18 adult attendees, and 15 breakfast club staff to determine the uses and impacts associated with holiday breakfast club participation and to investigate potential areas for future development of holiday food provision. Findings highlighted a need for holiday food provision and revealed a multitude of nutritional, social, and financial benefits for those who accessed holiday breakfast clubs. Areas for further development and investigation are discussed in addition to implications for UK food and educational policies.